GIANT CELL TUMOR WITH VERTEBRAL ANEURYSMATIC BONE CYST IN A YOUNG – A CASE REPORT - Letícia Rodrigues Martinez Pucciarelli; Maria Carolina Franco da Cunha; Izabela Spereta Moscardini; Daniela Alari Chedid; Marcela Teixeira Oliveira de Bruno Paiva; Mateus Miyasaka; Carla Campos Petean Silva; Rian Souza Vieira (Coluna/Columna)
ABSTRACT Objective: To report a case of giant cell tumor (GCT) in conjunction with an aneurysmal bone cyst (ABC) in the lumbar spine (L4) of a young with post-treatment recovery. Introduction: Giant cell tumor (GCT) is a benign and aggressive bone neoplasm, frequently located in the knees, distal femur, and proximal tibia, and is rare in the spine. It can, and frequently does, coexist with aneurysmal bone cyst (ABC), also benign and locally aggressive. The diagnosis requires clinical and radiological correlation. Case report: A young patient with initially mild low back pain, which progressively limited the patient until it reached incapacitating and bedridden levels. He sought care at different levels of health care on numerous occasions and for months until he was admitted to a tertiary hospital. After imaging tests, a fracture of the body of the fourth lumbar vertebra (L4) was observed, with a pathological appearance and a compressive mass effect on the neural elements at the same level. After surgical treatment and open biopsy, the histology of the mass at L4 was identified as a giant cell tumor with an aneurysmal bone cyst component (histology, pathology, and immunohistochemistry). He underwent surgeries for clinical stabilization and excision of the recurrent and locally aggressive tumor mass, in addition to performing embolization of the tumor mass by radio intervention and adjuvant use of Desonumab. Conclusion: Benign tumors such as aneurysmal bone cysts and giant cell tumors, although rare in the spine, can confuse diagnoses and are locally aggressive. Such pathology should be treated in a tertiary health service by a team specialized in orthopedics and spine surgery, as well as with multidisciplinary assistance and follow-up consisting of a surgeon, interventional radiologist, oncologist, and related specialties. The need for immunomodulatory drugs is present. Level of Evidence V; Case Report.